FRI0515 Effectiveness of direct-acting antiviral therapy on cryoglobulinemia associated with hepatitis c virus. (12th June 2018) - Zegarra Mondragon, S.; Quiñones, J.R.; Bachiller Corral, J.; Vazquez Diaz, M.
Abstract : Background: Hepatitis C virus (HCV) is the most frequent cause of mixed cryoglobulinemia, reaching up to 30%–50% of patients with chronic infection. Cryoglobulinemia can manifest as arthritis, vasculitis, hypocomplementemia, peripheral neuropathy or renal involvement. A new direct-acting antiviral therapy against HCV is available for 4 years, and it achieves a sustained virologic response, close to the definition of cure for this viral infection. Objectives: To evaluate the effectiveness of treatment with direct-acting antivirals in HCV- associated cryoglobulinemia and its clinical manifestations. Methods: In a retrospective cross-sectional observational study, we enrolled all consecutive patients with positive serum cryoglobulins and HCV infection with high viral load. Patients with or without associated rheumatological or systemic manifestations were included. All of them were treated with a combination of the new antivirals: sofosbuvir +ledipasvir, or ombitasvir +paritaprevir + ritonavir+dasabuvir; during 8 to 24 weeks, between January 2014 and December 2016. Post treatment blood studies were made in all patients during the first year. Seronegativization of cryoglobulins and improvement of associated clinical manifestations after treatment were analysed. Results: Thirty patients were included, 24 (80%) women. The median age of was 61.4 years. The HCV genotype: 1B in 76.6%, 1A in 16.6% and type 4 in the rest. Eighteen (60%) patients had systemic manifestations: 11 had joint involvement, 11 hypocomplementemia, 8 had leukocytoclastic vasculitis or skin ulcers, 5 Raynaud's phenomenon, 5 sensory-motor peripheral neuropathy, 3 renal involvement with glomerulonephritis, 2 Sjögren's syndrome and 1 patient with autoimmune hemolytic anaemia. The sustained viral response was achieved in 29 patients (96.6%), maintaining an undetectable viremia after finishing the treatment. Cryoglobulins were negativized in 22 (73%) of patients, and complement was normalised in 36% of those who had hypocomplementemia before treatment. There was a clinical improvement in 54.2% of patients with previous associated rheumatologic or systemic manifestations. The artrhitis and cutaneous vasculitis had better response than the other manifestations. No significant correlations were found between the serological and clinical responses. Conclusions: Direct-acting antiviral therapy is very effective against HCV infection. It is also useful for the treatment of mixed cryoglobulinemia, negativizing cryoglobulins in almost 3/4 of the cases, and with clinical response in more than half of the patients, being more favourable in the cases of joint involvement and cutaneous vasculitis. Disclosure of Interest: None declared